Customer Satisfaction Moderates Service Quality, Timeliness, and Price on Customer Loyalty in Logistics Service Companies (Study on Logistics Companies in North Surabaya) - Arisanti, Dian; Budiono, Eko; Suyanto, Suyanto (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
In today’s increasingly complex and competitive business world, maintaining and enhancing customer loyalty is crucial for the long-term success of a company. This study aims to investigate the influence of service quality, timeliness, and competitive pricing on customer loyalty, with customer loyalty as a moderation. in the Logistics Service Company, the research method used is a quantitative approach by collecting data from 45 respondents who are customers of the Logistics Service Company. Data were analyzed using SEM PLS software to evaluate the influence of each variable on customer loyalty. The research results show that Customer Satisfaction (Z) as a moderator of Service Quality (X1) and Price (X3) significantly positively affects Customer Loyalty.